Dataset "Strain data from a superconducting magnet coil, measured using optical fibre segment interferometry" - James, Stephen W.; Barrington, James; Staines, Stephen; Tatam, Ralph P. (Cranfield University, 2025)
An array of optical fibre segment interferometers were deployed in a superconducting magnet to monitor the strain during energisation of the coil. Data was recorded as the current was increased from 0 amps to 90 amps, and then decreased to 0 Amps.
The data provided consists of a time series of the strain record around the entire circumference of the coil, and over 1 quadrant of the coil.
Keywords: optical fibre sensors; fibre segment interferometry; interferometry; high temperature superconductor; superconducting magnet; cryogenic